Beyond the need to boast: cost concealment incentives and exit in Cournot duopoly - Jos Jansen (Max Planck Institute for Research on Collective Goods, 2009)
This paper studies the incentives for production cost disclosure in an asymmetric Cournot duopoly. Whereas the efficient firm (consumers) prefers information sharing (concealment) when the firms choose accommodating strategies in the product market, the firm (consumers) may prefer information concealment (sharing) when it can exclude its competitor from the market. Hence, the rankings of expected profit and consumer surplus can be reversed if exit of the inefficient firm is possible. Although the efficient firm has stronger incentives to share information when it shares strategically, there remain cases in which the firm conceals information in equilibrium to induce exit.
Keywords: D82; L13; 330; Cournot duopoly; information disclosure; exit; cost asymmetry; precommitment